2016
DOI: 10.1111/mec.13538
|View full text |Cite
|
Sign up to set email alerts
|

A high frequency of allopolyploid speciation in the gymnospermous genus Ephedra and its possible association with some biological and ecological features

Abstract: The origin and evolution of polyploids have been studied extensively in angiosperms and ferns but very rarely in gymnosperms. With the exception of three species of conifers, all natural polyploid species of gymnosperms belong to Ephedra, in which more than half of the species show polyploid cytotypes. Here, we investigated the origin and evolution of polyploids of Ephedra distributed in the Qinghai-Tibetan Plateau (QTP) and neighbouring areas. Flow cytometry (FCM) was used to measure the ploidy levels of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(50 citation statements)
references
References 100 publications
(100 reference statements)
1
48
0
1
Order By: Relevance
“…Previous reports suggested that the two Old World tetraploid Ephedra species, E. intermedia and E. sinica, were positioned in a monophyletic clade (Huang et al 2005;Qin et al 2013;Wu et al 2016), partially due to the lack of significant phenotypes and weak phylogenetic signals. In this work, based on the sequence variations of four cpDNA fragments, we detected 14 haplotypes, which suggested that these two species formed a monophyletic clade and that E. intermedia is paraphyletic due to the populations WQ and BYBL (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Previous reports suggested that the two Old World tetraploid Ephedra species, E. intermedia and E. sinica, were positioned in a monophyletic clade (Huang et al 2005;Qin et al 2013;Wu et al 2016), partially due to the lack of significant phenotypes and weak phylogenetic signals. In this work, based on the sequence variations of four cpDNA fragments, we detected 14 haplotypes, which suggested that these two species formed a monophyletic clade and that E. intermedia is paraphyletic due to the populations WQ and BYBL (Fig.…”
Section: Discussionmentioning
confidence: 97%
“…In the Himalaya–Hengduan Mountains region, limited biogeographic studies manifested that diploid and derivative polyploids colonizing different distribution areas (Liang et al, 2015; Wu et al, 2016), with some polyploids tending to occur at high altitudes, such as Aconitum (Yuan and Yang, 2006), Allium przewalskianum (Cui et al, 2008), and Anaphalis nepalensis (Meng et al, 2014). Although geographical segregation of cytotypes has long been recognized, the underlying mechanisms creating these patterns remain poorly understood (McIntyre, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In gymnosperms, WGDs have been reported for conifers, G. biloba and cycads (a likely shared WGD) 14,29,30 . Although recent polyploidy seems common in extant Ephedra 31 , evidence for ancient WGDs in gnetophytes is missing (Supplementary Information and Supplementary Fig. 7), except for a WGD in Welwitchia which is likely to have occurred after the divergence of its lineage from that leading to Ephedra (Supplementary Fig.…”
Section: ('Lack Of') Whole Genome Duplicationmentioning
confidence: 99%